Degradation of lignocellulosic matrix of oilseed cakes by solid‐state fermentation: fungi screening for enzymes production and antioxidants release. (30th August 2021) - Sousa, Daniel; Salgado, José M; Cambra‐López, Maria; Dias, Alberto CP; Belo, Isabel
Abstract: BACKGROUND: Vegetable oils are yearly produced in large amounts generating solid by‐products, the oilseed cake (OC). OCs are lignocellulosic materials that have been used for animal feed with some limitations due to high fibre content from the plant cell walls. Biotechnological processes can help to overcome these limitations and contribute to up‐grading such by‐products, enhancing their nutritional value as feed ingredients. RESULTS: All fungal species were able to decrease neutral detergent fibre and acid detergent fibre in all by‐products. Additionally, relevant enzymes were produced by the three fungi studied resulting in an improved antioxidant capacity of all fermented OCs. Aspergillus niger led to the highest activity of cellulase (109 U g −1 ), xylanase (692 U g −1 ) and protease (157 U g −1 ) per dry OC matter and to the recovery of an extract rich in antioxidants, with the highest scavenging potential of free radicals and superoxide anion, iron chelation ability and reducing power. Rhyzopus oryzae produced the highest activity of β‐glucosidase (503 U g −1 ) and led to the highest liberation of total phenolic content (TPC). Principal components analysis showed that extracts with high antioxidant potential were obtained in solid‐state fermentation (SSF) with high enzymatic activity. A positive correlation was established between the action of β‐glucosidase and TPC. CONCLUSION: Within the same bioprocess it was possible to improve the nutritional value of OCs and to obtain relevant bioactive compounds such as lignocellulosic enzymes and phenolic compounds with antioxidant potential, resulting in a significant improvement of already valuable by‐products with commercial interest for animal feed. © 2021 Society of Chemical Industry.